Activities of xanthine oxidase, nitric oxide synthase, aromatase and level of cytochrome P450 1A1, 1A2 and 1B1 isoforms in rat upon parenteral genistein injections - Sumbaev, V.V.; Yasinska, I.M. (Біополімери і клітина, 2001)
It has been established that genistein inhibits the xanthine oxidase and nitric oxide synthase activity in the rat liver, lung and brain and decreases the aromatase activity and the enzyme level in the rat ovaries and uteri. Genistein has been also established as the inductor of the rat liver cytochrome P450 1A1, 1A2 and 1B1 isoforms. It has been shown in vitro that genistein is both the xanthine oxidase allosteric inhibitor, decreasing the superoxide generation, and the aromatase competitive inhibitor.